Telemetry System Design for Monitoring Electrical Energy in Residential Homes - Aprilia Mayangsari Adiaputri; Saadilah Rosyadi (Journal of Robotics, Automation, and Electronics Engineering, 2024)
This project aims to (1) create and design a telemetry system for monitoring electrical energy in residential homes, (2) determine the functional tests of each component used, and (3) determine the performance tests of the tools being made. The manufacturing and testing process for this tool was carried out at the Electrical Installation Laboratory, Vocational Faculty, Yogyakarta State University. The data analysis technique used is calculating the percentage error between the tool data created and standard measuring tool data. The results obtained are (1) an electrical energy monitoring system was produced with components in the form of an ACS712 current sensor, ZMPT101B voltage sensor, Arduino Uno, NodeMCU ESP8266, LCD 20×4, buzzer, and Blynk application. (2) The functional test results show that each component has a good accuracy value. The error percentage level from sensor testing shows a value below 5%, so the sensor accuracy is good. (3) The results of system performance testing also show quite high accuracy. The highest percentage error rate was 4.4%, namely in refrigerator current and energy-saving lamp power factor data.